2016
DOI: 10.1155/2016/1952947
|View full text |Cite
|
Sign up to set email alerts
|

Tropisetron Protects Against Acetaminophen-Induced Liver Injury via Suppressing Hepatic Oxidative Stress and Modulating the Activation of JNK/ERK MAPK Pathways

Abstract: Objectives. To investigate the protective effects of tropisetron on acetaminophen- (APAP-) induced liver injury in a mice model. Methods. C57BL/6 male mice were given tropisetron (0.3 to 10 mg/kg) 30 minutes before a hepatotoxic dose of acetaminophen (300 mg/kg) intraperitoneally. Twenty hours after APAP intoxication, sera alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels, hepatic myeloperoxidase (MPO), malondialdehyde (MDA), glutathione (GSH), and superoxide dismutase (SOD) activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
2
10
0
1
Order By: Relevance
“…In our experiment, the PA- and PH-induced hepatic oxidative damage was evidenced by the liver histopathological findings and the significant increased hepatic levels of MDA and NO and serum levels of 8-OH-Gua, with significant decreased hepatic GSH and total thiols among PA-only and PH-only treated groups when compared with the controls. These findings were in agreement with many studies [ 29 33 ].…”
Section: Discussionsupporting
confidence: 94%
“…In our experiment, the PA- and PH-induced hepatic oxidative damage was evidenced by the liver histopathological findings and the significant increased hepatic levels of MDA and NO and serum levels of 8-OH-Gua, with significant decreased hepatic GSH and total thiols among PA-only and PH-only treated groups when compared with the controls. These findings were in agreement with many studies [ 29 33 ].…”
Section: Discussionsupporting
confidence: 94%
“…Some researchers have suggested that ERK is one of the most important mediators in liver injury. The study by Fu et al showed that acetaminophen-induced liver injury was ameliorated by suppressing the JNK/ERK pathway [ 51 ]. Liu et al found that the ERK pathway can regulate matrix metalloproteinase-1 induction in hepatic stellate cells [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…By a gene ontology and KEGG analysis of co‐expressed mRNA, we found that lncRNA might maintain hepatic homeostasis and the damage repair process through protein processing in the endoplasmic reticulum, MAPK, and PPAR signaling pathway. Several studies have reported that the MAPK and PPAR signaling pathway play important regulatory roles in the progression of AILI . The endoplasmic reticulum protein synthesis pathway may be associated with endoplasmic reticulum stress, which can be induced by various pathophysiological situations including ischemic injury, viral infection, drug‐induced liver injury and metabolic diseases, and lead to cell apoptosis …”
Section: Discussionmentioning
confidence: 99%